Comportamiento de los depósitos en el sector financiero de la región Loreto periodo 2014 - 2018 - Pinedo Olortegui, Maria Elena (2021)
The research work Behavior of deposits in the financial sector of the Loreto region reflects the close relationship that exists with the evolution of the regional economy and the culture of savings, in addition, to be related to the financial education that entities may have performed Financial The objective of the research is to determine the behavior of deposits in the financial sector of the Loreto region during the period 20144 - 2018, the research is applied, with a quantitative approach of descriptive level, the design is not experimental, because it is not variable manipulation The results conclude that the growth rate of deposits in the Loreto region in the financial sector is 43.50%; Within the structure of deposits, it is the savings that have the highest growth rate of 43.2%. In the banking sector it is the multiple banking that captures 81.2% and in the non-banking sector it is the Municipal Savings and Credit Institutions that stand out with a 99% deposit collection. However, in all financial deposits have not had a sustained growth year after year.